The interior architecture theory reader - Marinic, Gregory (Routledge, 2018)
The Interior Architecture Theory Reader presents a global compilation that collectively and specifically defines interior architecture. Diverse views and comparative resources for interior architecture students, educators, scholars, and practitioners are needed to develop a proper canon for this young discipline. As a theoretical survey of interior architecture, the book examines theory, history, and production to embrace a full range of interior identities in architecture, interior design, digital fabrication, and spatial installation. Authored by leading educators, theorists, and practitioners, fifty chapters refine and expand the discourse surrounding interior architecture.--Provided by publisher.